A model for underwater security in communication using Secret Key Algorithm and Node Value - Shuvo, MD. Saidul Arifin; Firdaus, Mustafa Tamim (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.